Highly active Pd–Ni nanocatalysts supported on multicharged polymer matrix. Issue 24 (10th November 2017) - Sultanova, Elza D.; Samigullina, Aida I.; Nastapova, Natalya V.; Nizameev, Irek R.; Kholin, Kirill V.; Morozov, Vladimir I.; Gubaidullin, Aidar T.; Yanilkin, Vitaliy V.; Kadirov, Marsil K.; Ziganshina, Albina Y.; Konovalov, Alexander I.
Abstract : In this article, we report the synthesis of mono- and bimetallic Pd–Ni nanocomposites supported on a multicharged polymeric matrix for catalytic applications. Abstract : In this article, we report the synthesis of mono- and bimetallic Pd–Ni nanocomposites supported on a multicharged polymeric matrix for catalytic applications. The morphology and catalytic properties of the composites depend on the Pd–Ni ratio. In the Suzuki–Miyaura coupling reaction, the composite with an equal amount of palladium and nickel is the most active and the reaction occurs within six hours in water at room temperature.